Rapid diagnosis and treatment of severe tricyclic antidepressant toxicity. (14th October 2015) - Clark, Simon; Catt, Jerry W; Caffery, Terrell
Abstract : A woman in her mid-50s contacted her social worker and expressed intent to commit suicide by ingesting prescription medications. On arrival of emergency responders, the patient was found unconscious with an empty bottle of amitriptyline. Time of ingestion was estimated using the social worker's contact with local authorities. The patient's presentation at the emergency department (ED) exemplified tricyclic antidepressant toxidrome with a poor prognosis, based on measurable criteria and physical findings. Respiratory and cardiovascular collapse was managed emergently. Haemodynamic status and EKG findings responded in a stepwise fashion with therapy in the ED and intensive care unit. Full clinical recovery took 7 days, and the patient was subsequently transferred to an in-patient psychiatric facility for further evaluation. Eight days later, she was discharged home with no neurological sequelae.